Influence of socio-cultural environment on becoming and functioning of weaving - Tischuk, M. V. (History of science and technology, 2014)
In the article intercommunication of the phenomena of социокультурной environment of Right-bank Polesye is considered with becoming and development of the phenomenon of weaving on these territories. Consideration of him in the sentinel-spatial measuring allowed retrospectively to trace influence of surroundings on development of culture and technology of weaving, and also factors of positive and negative influence in local displays.